ONSITE SANITATION GOVERNANCE TOOLS FOR SMALL MUNICIPALITIES – FIRST STEPS FROM SANTA CATARINA STATE, SOUTH BRAZIL - Trevisan, Alexandre Bach; Pereira, Luciane Dusi; Sezerino, Pablo Heleno (Revista AIDIS de ingeniería y ciencias ambientales: Investigación, desarrollo y práctica, 2023)
Promoting sanitation solutions are more than just choosing the right technology. The need for stakeholders’ cooperation and engagement challenges small municipalities to consider fecal sludge management (FSM) and simplified sewerage approaches, not only conventional systems, promoting a flexible suite of services and emerging governance discussion in this complex scenario. In this paper, we conducted 10 semi-structured key informant interviews (KII) and show 15 implemented governance tools in 5 municipalities with less than 10,000 inhabitants, in Santa Catarina State, in the Brazilian southern region. None of the researched municipalities showed a systematized framework and the governance structure is composed of dispersed tools, mainly developed in response to a public attorney, who acts as a blind sponsor of onsite solutions, calling other stakeholders for action. Onsite sanitation performs a relevant role to achieve service universalization, this paradigm shift requires a new governance structuring model that considers FSM as a part of this ecosystem seems to be the trail first step especially where the conventional approach does not always reach financial sustainability.